Overexpression of miRNA-21 Promotes the Proliferation and Invasion in Hepatocellular Carcinoma Cells via Suppressing SMAD7 - Wang, Yan (Technol Cancer Res Treat, 2019)
PURPOSE: This study aimed to explore the molecular mechanism of microRNA-21 and smad family member 7 in hepatocellular carcinoma. METHOD: A total of 57 participants were divided into control group (healthy participants, n = 10) and hepatocellular carcinoma group (hepatocellular carcinoma patients, n = 37). The expression of microRNA-21 levels were first detected in these two groups. Cell transfection was performed on hepatoma cell lines, followed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and Transwell assay to reveal proliferation and invasion ability. Furthermore, the relation between microRNA-21 and smad family member 7 was revealed by luciferase reporter gene and RNA immunoprecipitation assay. Finally, a transplantation tumor model of breast cancer in mice was constructed. RESULTS: The serum indicators including α-alanine aminotransferase, aspartate aminotransferase, and albumin were differentially expressed between hepatocellular carcinoma group and control group. Compared to the control group, there was a high expression of microRNA-21 in hepatocellular carcinoma group. Low expression of microRNA-21 inhibited the proliferation and invasion of HepG2.2.15 and Huh7-1.3 cells. Luciferase reporter gene and RNA innumoprecipitation assay showed that smad family member 7 was the target gene of microRNA-21. Moreover, mice model analysis showed that microRNA-21 might regulate the growth of the transplanted tumors in mice by targeting smad family member 7. CONCLUSION: The upregulated microRNA-21 might participate in the proliferation and migration in cells of hepatocellular carcinoma via suppression of smad family member 7. Furthermore, serum indicators such as alanine aminotransferase, aspartate aminotransferase, and albumin might be used as serum diagnostic markers for hepatocellular carcinoma.